Inheritors of the Yellow River: the relationship of heritage making practices to cultural self-confidence in China - Wanlin Zhang; Stuart Walker; Martyn Evans; Julia Bennett (International Journal of Anthropology and Ethnology, 2021)
Abstract Through active involvement in UNESCO’s ICH (Intangible Cultural Heritage) programme, China has developed its own framework to support traditional making practices. To examine the ‘characteristics’ of heritage crafts preservation in China, we undertook empirical research in the Yellow River basin. Our research involved in-depth observations and key informant interviews with a range of highly accomplished craftspeople who have inherited their particular expertise from their family and have been officially designated ICH Inheritors. Through our qualitative research with inheritors, a businessperson and a government official, we identified various support mechanisms employed by the Chinese government that aim to protect traditional culture while also recognising outstanding individuals. We also found that ICH Inheritors play an important role in raising cultural awareness and enhancing cultural confidence through their creative activities and making practices, craft businesses and transfer of expertise. Based on the findings, potential areas where designers may collaborate with inheritors were identified.